Isolation and phylogenetic characterization of arboviruses circulating among phlebotomine sandflies in parts of North Rift, Kenya - Koskei, Edith; Langat, Solomon; Mutisya, James; Mulwa, Francis; Lutomiah, Joel; Koka, Hellen; Oyola, Samuel O.; Waihenya, Rebecca; Mabeya, Sepha N.; Sang, Rosemary (Frontiers in Virology, 2024)
Background: Until recently, arbovirus surveillance mainly focused on mosquito and tick vectors, resulting in the discovery of several mosquito and tick-borne arboviruses. However, the role of sandflies in arbovirus transmission and disease has remained largely unexplored. This study sought to isolate and characterize arboviruses from phlebotomine sandflies from selected pastoral ecozones in the North Rift region of Kenya.Methods: Sandflies were collected from selected sites in North Rift Kenya between 2015 and 2018. They were sorted and pooled by sex, site and collection date. The pools were homogenized and inoculated onto Vero cells for virus isolation. The positive pools were analyzed by polymerase chain reaction targeting different arboviruses. The isolates were further characterized by high throughput sequencing using Illumina Miseq platform.Results: Approximately 28,226 sandflies translating to 824 pools were sampled from selected regions. Eleven showed reproducible cytopathic effects on Vero cells. We identified five arboviruses, sindbis (n=4) from Kacheliba and Baringo, Chandipura (n=4) from Turkana and Baringo, Koutango (n=1) and Ntepes (n=1) from Baringo and Bogoria (n=1) from Kacheliba. The percent identities of the identified viruses were approximately 80% to 98% compared to known viruses in GenBank, suggesting some of them could be novel viruses.This study successfully isolated and characterized five arboviruses from sandflies.The findings suggest that sandflies are potential hosts of a wide range of arboviruses and are therefore important vectors to consider in arbovirus surveillance and evaluated for their ability to transmit them. Further studies are needed to determine the public health importance and extent of exposure of these viruses to humans and livestock populations.